Effect of corticosteroid therapy on influenza-related mortality: a systematic review and meta-analysis - Rodrigo, Chamira; Leonardi-Bee, Jo; Nguyen-Van-Tam, Jonathan S.; Lim, Wei Shen (Oxford University Press, 2015)
Background: Most studies have reported that corticosteroid therapy adversely influences influenza-related outcomes.